Pathogenetic role of endothelial dysfunction of periodontal vessels in atients with type II diabetes mellitus in the development and progression of generalized periodontitis - Різник, Світлана Степанівна; Різник, Юрій Богданович (Actual Dentistry, 2019)
Summary. An important achievement in settling the issue of pathogenesis of generalized periodontitis in the settings of diabetes mellitus is the study of endothelial dysfunction of periodontal vessels. Special emphasis in the induction of vascular disorders is placed on endothelin-1, which is a powerful endogenous vasoconstrictor. The aim of our study was to analyze the correlation between clinical manifestations of generalized periodontitis, functional changes in its vascular system in patients with type II diabetes and the level of endothelin-1 vasoconstrictor in the oral fluid depending on the course and severity of generalized periodontitis. Material and methods. Complex clinical and laboratory studies of 34 patients with generalized periodontitis in the settings of type 2 diabetes mellitus aged 40– 65 and 10 patients with clinically intact periodontal tissues without somatic pathology were performed. Results. An increase in the endothelin-1 level in the examined patients indicates intensified vasoconstriction. A direct correlation between the endothelin-1 level, the severity of generalized periodontitis and the degree of compensation of the diabetes mellitus was established. Conclusions. Endothelial dysfunction of the microcirculatory bloodstream of the periodontal tissues in the settings of type 2 diabetes mellitus has pathogenetic significance in the development and course of the generalized periodontitis. Evaluation of the endothelin-1 level in the oral fluid can be a diagnostically significant factor for determining the severity of the pathological process and the treatment efficacy of patients with generalized periodontitis in the settings of diabetes mellitus. Key words: generalized periodontitis, diabetes mellitus, endothelial dysfunction, endothelin-1.